HUBUNGAN KEMAMPUAN MENGGUNAKAN TEKNOLOGI KEPERAWATAN DENGAN CARING MAHASISWA PROFESI NERS DI SEKOLAH TINGGI ILMU KESEHATAN WILAYAH SURABAYA : The Relationship Between Technological Skill Competency and Caring of Nursing Profession Students in Surabaya Region - Ignata Yuliati; Marcellina Rasemi Widayanti (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2020)
Technology is an integrated presence between science and machines. Information technology in nursing includes knowledge, attitudes and skills. These three things are needed by a health care profession in their daily work. The ability of nurses to use nursing technology is a form of caring. Nurse caring behavior is very important in fulfilling patient satisfaction, therefore students' understanding of technology as a form of caring in nursing needs to be instilled since the period of education. The purpose of this study was to identify the relationship between the technological skill competency in nursing and caring of nursing profession students. The research method used in this study is correlation analytic with cross sectional approach. Questionnaire was utilized to gather the needed data and information. The subjects of this study were 90 nursing students, total sampling was applied to gained participants. Respondents met the inclusion criteria, namely studying at STIKes in the Surabaya region, being willing to be respondents, and graduating a bachelor's degree in nursing, a maximum of one year before continuing to Ners profession student. The results showed that there was a significant relationship between the ability to use technology (medical devices) and caring of Ners professional students (p = 0.000; r = 0.630. There was a significant relationship between the ability to use technology (Information and Communication Technology) and caring (p = 0.000; r = 0.469). The ability to use technology makes nurses understand the patient as a whole or holistic human. If the nurse understands the patient completely then he will understand all aspects of the patient as a unique person, this will help patients to develop and accelerate the healing process. The ability of nurses to use technology is an expression of caring in nursing, where caring and technology are an integral part. Technology plays an important role in health care, technology is used to improve patient safety, save lives patient and support nurses in their job. Teaching caring from the time of education is very important because this is the first stage for nursing students to learn the value and meaning of the nursing profession.